Cyst of Montgomery: An uncommon adolescent breast lump - Afnan F Almuhanna; Asma F Almuhanna; Reem S Alzuabi; Reem A Alshamlan; Fatimah H Almarhoon (Wolters Kluwer Medknow Publications, 2020)
Reports of the incidence of the cyst of Montgomery, a rare condition of the breast, affecting mainly adolescent female, are scarce in the literature. This cyst develops from an obstruction of the small papular projections at the edge of the areola called Montgomery tubercles. It could be a simple asymptomatic mass or an inflamed symptomatic mass. We report two cases encountered this year. The first case was a 15-year-old female who complained of bilateral breast pain and a right breast mass. Laboratory tests were unremarkable. A diagnosis of noninflamed Montgomery cyst based on clinical and sonographic examination was made. An antibiotic was recommended. The second case was a 13-year-old female who complained of pain and swelling with redness in the right breast. Laboratory tests were unremarkable. Sonographic examination revealed a right retroareolar cyst containing turbid echogenicity with surrounded hyperemia. A diagnosis of inflamed Montgomery's cyst was made. Medical treatment was successful without any surgical intervention. Both patients had favorable outcomes at follow-up visits. This stresses the importance of a proper recognition of the pathology, incidence, diagnosis and management of the cyst of Montgomery in the pediatric age group.